Method for preparing analcime using lithium slag

Through the short process method of lithium slag pickling and decomposition removal and low-temperature wet activation, high crystallinity zeolites were prepared, which solved the problems of high cost and environmental risks of lithium slag, and achieved high-value utilization of lithium slag and reduced zeolite production costs.

CN119503834BActive Publication Date: 2025-04-18SICHUAN IND ENVIRONMENT MONITORING & RES INST

Patent Information

Application Number
CN202510090904.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-18
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The prior art has high costs, high energy consumption and the need for additional raw materials in the comprehensive utilization of lithium slag, making it difficult to effectively utilize lithium slag, and the accumulation of lithium slag leads to environmental risks.

Method used

Lithium slag is used as raw material, and the high crystallinity zeolite is prepared by short-process methods of pickling and impurity removal, low-temperature wet activation and hydrothermal reaction, avoiding the steps of calcination activation and adding raw materials.

Benefits of technology

The high-value utilization of lithium slag has been achieved, the production cost of zeolite has been reduced, energy consumption has been reduced, and environmental pollution has been avoided, opening up a new way to comprehensive utilization of lithium slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503834B_ABST
    Figure CN119503834B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing analcime using lithium slag, and belongs to the field of zeolite preparation. The method comprises the following steps: acid washing and impurity removal: mixing the lithium slag with an inorganic acid solution, stirring and reacting at 50-70°C for 0.5-3h, and then filtering, washing, and drying in sequence to obtain the lithium slag after impurity removal; activation: mixing the lithium slag after impurity removal with a NaOH solution, stirring and reacting continuously at 75-95°C for 35-72h, and aging for 10-30 min to obtain a mixture colloid; crystallization: hydrothermally reacting the mixture colloid at 110-130°C for 24-72h, and then filtering, washing, and drying in sequence to obtain analcime crystal material. The method uses lithium slag after lithium extraction by leaching of spodumene sulfuric acid method as raw material, and can obtain high-purity analcime crystals by controlling the NaOH concentration, activation temperature and time during activation, and the temperature and time during hydrothermal reaction without calcination activation and without adding raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of zeolite preparation, and in particular to a method for preparing analcime by utilizing lithium slag. Background Art

[0002] Lithium slag is the solid waste generated in the process of extracting lithium carbonate and lithium hydroxide from lithium ore. Usually, 8 to 10 tons of lithium slag will be produced for every ton of lithium salt produced. With the rapid growth in demand for battery-intensive application scenarios such as new energy vehicles in my country, more than 15 million tons of lithium slag are discharged in the process of lithium ore extraction each year. The large accumulation of lithium slag not only causes a waste of land resources, but also poses serious environmental risks to the surrounding soil and water environment. At present, the comprehensive utilization of lithium slag is mainly concentrated in the field of building materials. This disposal method is still in the "waste treatment" stage and has low economic value. Therefore, using lithium slag to produce high value-added products and enhance economic value is of great significance to extending the lithium ore processing industry chain and promoting the efficient use of resources.

[0003] Analcime (NaAlSi 2 O 6 ·H 2 Analcime is a sodium aluminum silicate mineral with a cage structure. Silicon oxygen and aluminum oxygen tetrahedrons form crystals with a unique pore structure by sharing oxygen atoms on the vertices. It has the characteristics of high specific surface area, high porosity, and strong ion exchange capacity. Analcime is widely used in industry, agriculture, chemical industry, environmental protection and other fields. For example, it can be used as a soil conditioner to increase the exchange capacity of salts in the soil and improve soil fertility; it can be used to extract non-ferrous metals from lake water, groundwater and other water bodies, or to recover metal ions from industrial wastewater by utilizing the selective adsorption of heavy metal ions by analcime; analcime can also be used as a catalyst carrier, chromatographic column filler, etc. in the field of petrochemicals. Natural analcime has a small reserve and low grade, which cannot meet the needs of industrial production. At present, it is mostly synthesized artificially using chemical reagents and raw materials.

[0004] Chinese patent CN115231585 A discloses a method for preparing analcime mesoporous material from coal gangue, wherein the coal gangue is subjected to a series of physical and chemical pretreatments and high-temperature activation treatments, magnesium salts and nitrilotriacetic acid are added, and then analcime products with flower-like morphology are obtained through high-temperature hydrothermal reaction. Chinese patent CN115818659 A discloses a method for preparing analcime from siliceous aluminum tailings, wherein analcime is obtained through acid leaching, impurity removal, calcination activation and hydrothermal reaction. The above methods all use calcination activation, which consumes more energy, and there are also more steps and the need for additional raw materials, resulting in a high synthesis cost. Therefore, a method for directly preparing analcime using lithium slag as raw material, without the need for additional raw materials and calcination activation, is developed, which reduces the production cost of analcime while realizing the high-value utilization of lithium slag, and is of great significance to opening up new ways for the comprehensive utilization of lithium slag. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing analcime using lithium slag. The method uses lithium slag after lithium extraction from spodumene by sulfuric acid method as raw material, and synthesizes high-crystallinity analcime in a short process without calcination activation and without adding external raw materials, thereby realizing high-value comprehensive utilization of lithium slag and reducing the production cost of analcime.

[0006] The technical solution of the present invention is as follows:

[0007] The present invention provides a method for preparing analcime using lithium slag, comprising the following steps:

[0008] (1) Acid washing and impurity removal: Mix the lithium slag with an inorganic acid solution, stir and react at 50-70°C for 0.5-3h, and then filter, wash and dry in sequence to obtain the lithium slag after impurity removal;

[0009] (2) Activation: Mix the lithium slag after impurity removal with NaOH solution, react with continuous stirring at 75-95°C for 35-72 hours, and age for 10-30 minutes to obtain a colloid mixture;

[0010] (3) Crystallization: The colloid mixture is subjected to a hydrothermal reaction at 110-130°C for 24-72 hours, and then filtered, washed, and dried in sequence to obtain analcime crystal material.

[0011] In the activation step, if the NaOH solution is replaced with NaBH 4 Solution or Na 2 CO 3 The products obtained by activation are all NaP molecular sieves.

[0012] In a specific embodiment, the lithium slag is the lithium slag after lithium is extracted by leaching spodumene with sulfuric acid method; the particle size of the lithium slag is ≤200 mesh.

[0013] In a specific embodiment, the inorganic acid in step (1) is at least one of hydrochloric acid, sulfuric acid, and nitric acid; the concentration of the inorganic acid solution is 0.08-0.5 M; and the solid-liquid ratio of the lithium slag to the inorganic acid solution is 1 g:(10-20) mL.

[0014] Preferably, the concentration of the inorganic acid solution in step (1) is 0.08-0.3 M, the stirring reaction temperature is 50-60° C., and the reaction time is 0.5-2 hours.

[0015] More preferably, the concentration of the inorganic acid solution in step (1) is 0.1-0.2 M, the stirring reaction temperature is 50-60 °C, and the reaction time is 1-2 hours.

[0016] The main purpose of the pickling and impurity removal of the present invention is to remove the impurity elements such as Ca, Mg, Fe, S, etc. contained in the lithium slag, the presence of which will seriously affect the n(SiO 2 ) / n(Al 2 O 3 ) and step (2) produce intermediate substances that form analcime, which ultimately affect the crystallization of analcime, and are therefore necessary steps for the preparation of analcime. Within the concentration range of 0.08-0.5 M inorganic acid involved in the present invention, there is no significant difference in the impurity removal effect.

[0017] In one embodiment, the SiO in the lithium slag after impurities removal in step (1) 2 The content is 30%~70%, Al 2 O 3 The content is 20%~40%.

[0018] Preferably, the SiO in the lithium slag after impurities removal in step (1) 2 The content is 50%~70%, Al 2 O 3 The content is 20%~30%.

[0019] In one embodiment, the SiO in the lithium slag after impurities removal in step (1) 2 The content is 60%~70%, Al 2 O 3 The content is 25%~30%.

[0020] n(SiO 2 ) / n(Al 2 O 3 ) is one of the important factors affecting the zeolite crystallization nucleation speed and the type of zeolite formed. In the present invention, if SiO 2 and Al 2 O 3 If the composition exceeds the specified range, P-type molecular sieve is easily generated.

[0021] In one specific embodiment, the activation reaction temperature in step (2) is 80-95°C, the reaction time is 40-60 hours, and the aging time is 20-30 minutes.

[0022] In one embodiment, the activation reaction temperature in step (2) is 85-95°C and the time is 40-50 hours.

[0023] In a specific embodiment, in step (2), the solid-to-liquid ratio of the lithium slag after impurities removal to the NaOH solution is 1 g: (50-150) mL.

[0024] In the present invention, the solid-liquid ratio of the lithium slag after impurity removal and the NaOH solution has an important influence on the nucleation and crystallization of zeolite and the type of zeolite. If the solid-liquid ratio is too low, the silicon and aluminum ions in the lithium slag cannot be fully dispersed into the solution; if the solid-liquid ratio is too high, the mass transfer time of the raw materials in the solution is long. The above factors ultimately affect the nucleation and crystallization of zeolite and the type of zeolite.

[0025] In one specific embodiment, in step (2), the concentration of the NaOH solution is 0.6-1.0 M.

[0026] In one specific embodiment, in step (2), the concentration of the NaOH solution is 0.7-0.9 M.

[0027] During activation, NaOH solution can destroy the structure of lithium slag, causing Si and Al in the lithium slag to dissolve in large quantities, thus accelerating the nucleation and crystallization of zeolite. + ) is an important component of zeolite. The concentration of NaOH solution also affects [SiO 4 ] and [AlO 4 ], resulting in different types of synthesized zeolite molecular sieves. Specifically in the present invention, if the concentration of the NaOH solution exceeds the range, analcime cannot be prepared. The concentration of the NaOH solution is strongly correlated with the other reaction conditions. For example, if the NaOH concentration is high, the reaction time of step (2) is short, or the reaction temperature should be lowered; if the NaOH concentration is low, the reaction time of step (2) should be appropriately extended, or the reaction temperature should be appropriately increased.

[0028] In one specific embodiment, in step (3), the hydrothermal reaction temperature is 120-130° C., and the reaction time is 36-60 hours.

[0029] In one specific embodiment, in step (3), the hydrothermal reaction temperature is 120-130° C., and the reaction time is 36-50 hours.

[0030] In the present invention, the NaOH concentration, activation temperature and time during low-temperature wet activation, and the temperature and time during the hydrothermal reaction have a great influence on the composition and structure of the reaction product. The present invention can obtain high-purity analcime crystals by controlling the NaOH concentration, activation temperature and time during activation, and the temperature and time during the hydrothermal reaction.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention adopts a low-temperature wet method to activate lithium slag, which greatly reduces energy consumption compared with the traditional high-temperature calcination activation method; and in the synthesis process, there is no need to add raw materials such as silicon source and aluminum source. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD pattern of the product prepared in Example 1;

[0034] Figure 2 This is the SEM characterization result of the product prepared in Example 1;

[0035] Figure 3 This is the XRD pattern of the product prepared in Example 2;

[0036] Figure 4 This is the XRD pattern of the product prepared in Example 3;

[0037] Figure 5 This is the XRD pattern of the product prepared in Example 4;

[0038] Figure 6 This is the XRD pattern of the product prepared in Comparative Example 1;

[0039] Figure 7 This is the XRD pattern of the product prepared in Comparative Example 2;

[0040] Figure 8 This is the XRD pattern of the product prepared in Comparative Example 3;

[0041] Fig. 9 This is the XRD pattern of the product prepared in Comparative Example 4;

[0042] Fig.10 This is the XRD pattern of the product prepared in Comparative Example 5;

[0043] Fig.11 This is the XRD pattern of the product prepared in Comparative Example 6. DETAILED DESCRIPTION

[0044] The present invention is further described below with specific examples, but the embodiments of the present invention are not limited thereto.

[0045] The raw material used in the embodiment of the present invention is lithium slag after lithium extraction from spodumene by sulfuric acid leaching, and its composition is as follows after detection by X-ray fluorescence spectrometer (XRF):

[0046] Element <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> CaO <![CDATA[SO 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[Na 2 The]]> <![CDATA[K 2 The]]> MgO Mass percentage (%) 59.12 25.33 5.16 7.54 1.07 0.55 0.44 0.13

[0047] Example 1

[0048] Prepare 100 ml of 0.1 M HCl solution, add 5 g of lithium slag with a particle size of less than or equal to 200 mesh, stir at 60 °C for 2 hours, filter, wash and dry to obtain SiO 2 Content 69.7%, Al 2 O 3 Lithium slag with a content of 27.7% and other components of about 2.6%.

[0049] Prepare 50 ml of 0.7 M NaOH solution, add 0.5 g of acid-washed lithium slag, stir in an oil bath at 90 °C for 45 hours, age for 20 minutes, transfer to a hydrothermal reactor lined with polytetrafluoroethylene, hydrothermally react at 120 °C for 45 hours, filter, wash and dry to obtain the product, whose XRD spectrum is shown in Figure 1 The diffraction peaks in the figure are consistent with the characteristic peaks of the analcime standard card PDF#76-0905. The diffraction peaks of 15.7°, 18.2°, 25.8°, 30.5°, 33.2°, and 35.7° correspond to the (211), (220), (400), (332), (413), and (512) crystal planes of analcime, respectively. Figure 2 This is the SEM characterization result of the sample in Example 1. It can be seen from the figure that the product is a high-purity analcime crystal with an average crystal particle size of about 8 μm. The BET specific surface area of ​​the obtained analcime is 17.78 m 2 / g.

[0050] Example 2

[0051] Configure 0.2 MH 2 SO 4 To 100 ml of the solution, add 5 g of lithium slag with a particle size of less than or equal to 200 mesh, stir at 60 °C for 1.5 hours, filter, wash and dry. 2 Content 69.5%, Al 2 O 3 Lithium slag with impurity content of 27.7% and other components of 2.8%.

[0052] Prepare 50 ml of 0.8 M NaOH solution, add 0.5 g of acid-washed lithium slag, stir in an oil bath at 80 °C for 48 hours, age for 20 minutes, transfer to a hydrothermal reactor lined with polytetrafluoroethylene, hydrothermally react at 120 °C for 48 hours, filter, wash, and dry to obtain the product analcime. Its XRD spectrum is shown in Figure 3 In the figure, the diffraction peaks of 15.7°, 18.2°, 25.8°, 30.5°, 33.2°, and 35.7° correspond to the (211), (220), (400), (332), (413), and (512) crystal planes of analcime, respectively; while the diffraction peaks of 12.3°, 21.6°, and 28.0° correspond to the (110), (211), and (310) crystal planes of NaP molecular sieve, respectively. The product is a mixture of analcime and a small amount of NaP molecular sieve, of which the mass proportion of analcime is about 90~95%.

[0053] Example 3

[0054] Configure 0.5 MH 2 SO 4To 100 ml of the solution, add 5 g of lithium slag with a particle size of less than or equal to 200 mesh, stir at 55 °C for 0.5 hour, filter, wash and dry. 2 Content 69.9%, Al 2 O 3 Lithium slag with impurity content of 27.8% and other components of 2.3%.

[0055] Prepare 50 ml of 0.6 M NaOH solution, add 0.5 g of acid-washed lithium slag, react in a water bath at 90 °C for 70 hours, age for 20 minutes, transfer to a hydrothermal reactor lined with polytetrafluoroethylene, react at 120 °C for 30 hours, filter, wash and dry to obtain the product, whose XRD spectrum is shown in Figure 4 In the figure, the diffraction peaks of 15.7°, 18.2°, 25.8°, 30.5°, 33.2°, and 35.7° correspond to the (211), (220), (400), (332), (413), and (512) crystal planes of analcime, respectively; while the diffraction peaks of 12.3°, 21.6°, and 28.0° correspond to the (110), (211), and (310) crystal planes of NaP molecular sieve, respectively. The product is a mixture of analcime and a small amount of NaP molecular sieve, of which the mass proportion of analcime is about 80~90%.

[0056] Example 4

[0057] Prepare 100 ml of 0.2 M HCl solution, add 8 g of lithium slag with a particle size of less than or equal to 200 mesh, stir in a 60°C water bath for 1.5 hours, filter, wash and dry. 2 Content 69.6%, Al 2 O 3 Lithium slag with impurity content of 27.7% and other components of 2.7%.

[0058] Prepare 40 ml of 0.85 M NaOH solution, add 0.5 g of acid-washed lithium slag, react in a water bath at 90 °C for 48 hours, age for 30 minutes, transfer to a hydrothermal reactor lined with polytetrafluoroethylene, react at 110 °C for 70 hours, filter, wash and dry to obtain the product analcime, whose XRD spectrum is shown in Figure 5 In the figure, the diffraction peaks of 15.7°, 25.8°, 30.5°, 33.2°, and 35.7° correspond to the (211), (400), (332), (413), and (512) crystal planes of analcime, respectively; while the diffraction peaks of 12.3°, 17.5°, 21.6°, and 28.0° correspond to the (110), (200) (211), and (310) crystal planes of NaP molecular sieve, respectively. The product is a mixture of analcime and a small amount of NaP molecular sieve, of which the mass proportion of analcime is about 70~85%.

[0059] Comparative Example 1

[0060] Prepare 100 ml of 0.1 M HCl solution, add 5 g of lithium slag with a particle size of less than or equal to 200 mesh, stir at 60 °C for 2 hours, filter, wash and dry. 2 Content 69.7%, Al 2 O 3 Lithium slag with impurity content of 27.7% and other components of 2.6%.

[0061] Prepare 50 ml of 0.85 M NaOH solution, add 0.5 g of acid-washed lithium slag, stir evenly and transfer into the polytetrafluoroethylene liner of the hydrothermal reactor, react at 120 °C for 24 hours, filter, wash and dry to obtain the product, and its XRD spectrum is shown in Figure 6 The diffraction peaks in the figure are consistent with the characteristic peaks of the standard card PDF#74-1787. The diffraction peaks 12.4°, 17.6°, 21.6°, 28.0°, and 33.3° correspond to the (110), (200), (211), (310), and (321) crystal planes of NaP molecular sieve, respectively. The product is NaP molecular sieve.

[0062] Comparative Example 2

[0063] Prepare 100 ml of 0.1 M HCl solution, add 5 g of lithium slag with a particle size of less than or equal to 200 mesh, stir at 60 °C for 2 hours, filter, wash and dry. 2 Content 69.7%, Al 2 O 3 Lithium slag with impurity content of 27.7% and other components of 2.6%.

[0064] Prepare 50 ml of 0.85 M NaOH solution, add 0.5 g of acid-washed lithium slag, and place in a 90 °C water bath for 48 hours, filter, wash, and dry. The XRD spectrum is shown in Figure 7 In the figure, the diffraction peaks of 12.4°, 17.6°, 21.6°, 28°, and 33.3° correspond to the (110), (200), (211), (310), and (321) crystal planes of NaP molecular sieve, respectively; the diffraction peaks of 6.1°, 23.2°, and 26.6° correspond to the (111), (533), and (642) crystal planes of NaX molecular sieve, respectively. The product is a mixture of NaP and NaX molecular sieves.

[0065] Comparative Example 3

[0066] Prepare 100 ml of 0.1 M HCl solution, add 5 g of lithium slag with a particle size of less than or equal to 200 mesh, stir in a 60 ℃ water bath for 2 hours, filter, wash and dry. 2Content 69.7%, Al 2 O 3 Lithium slag with impurity content of 27.7% and other components of 2.6%.

[0067] Prepare 50 ml of 0.5 M NaOH solution, add 0.5 g of acid-washed lithium slag, react in a water bath at 90 °C for 70 hours, age for 20 minutes, transfer to a hydrothermal reactor lined with polytetrafluoroethylene, react at 120 °C for 30 hours, filter, wash and dry to obtain the product, whose XRD spectrum is shown in Figure 8 The diffraction peaks in the figure are consistent with the characteristic peaks of the standard card PDF#74-1787. The diffraction peaks 12.4°, 17.6°, 21.6°, 28.0°, and 33.3° correspond to the (110), (200), (211), (310), and (321) crystal planes of NaP molecular sieve, respectively. The product is NaP molecular sieve.

[0068] Comparative Example 4

[0069] Prepare 100 ml of 0.2 M HCl solution, add 5 g of lithium slag with a particle size of less than or equal to 200 mesh, stir in a 60 ℃ water bath for 2 hours, filter, wash and dry. 2 Content 69.6%, Al 2 O 3 Lithium slag with impurity content of 27.7% and other components of 2.7%.

[0070] Prepare 50 ml of 0.8 M NaOH solution, add 0.5 g of acid-washed lithium slag, react in a water bath at 90 °C for 28 hours, age for 20 minutes, transfer to a hydrothermal reactor lined with polytetrafluoroethylene, react at 120 °C for 70 hours, filter, wash and dry to obtain the product, whose XRD spectrum is shown in Fig. 9 The diffraction peaks in the figure are consistent with the characteristic peaks of the standard card PDF#74-1787. The diffraction peaks 12.4°, 17.6°, 21.6°, 28.0°, and 33.3° correspond to the (110), (200), (211), (310), and (321) crystal planes of NaP molecular sieve, respectively. The product is NaP molecular sieve.

[0071] Comparative Example 5

[0072] Comparative Example 5 provides a method for preparing analcime using lithium slag, which is basically the same as Example 1, except that: the NaOH solution is replaced with NaBH 4 Solution.

[0073] The product obtained in Comparative Example 5 was characterized by X-ray diffraction, and its XRD pattern is shown in Fig.10The diffraction peaks in the figure are consistent with the characteristic peaks of the standard card PDF#74-1787. The diffraction peaks 12.4°, 17.6°, 21.6°, 28.0°, and 33.3° correspond to the (110), (200), (211), (310), and (321) crystal planes of NaP molecular sieve, respectively. The product is NaP molecular sieve.

[0074] Comparative Example 6

[0075] Comparative Example 6 provides a method for preparing analcime using lithium slag, which is basically the same as Example 1, except that: the NaOH solution is replaced with Na 2 CO 3 Solution.

[0076] The product obtained in Comparative Example 6 was characterized by X-ray diffraction, and its XRD pattern is shown in Fig.11 The diffraction peaks in the figure are consistent with the characteristic peaks of the standard card PDF#74-1787. The diffraction peaks of 12.4°, 17.6°, 21.6°, 28.0°, and 33.3° correspond to the (110), (200), (211), (310), and (321) crystal planes of NaP molecular sieve, respectively. The product is NaP molecular sieve.

[0077] By comparison, it can be seen that the NaOH concentration, activation temperature and time during low-temperature wet activation, and the temperature and time during the hydrothermal reaction have a key influence on the composition and structure of the reaction product. Compared with Example 1, there is a small amount of NaP in the products obtained by implementing 2, 3, and 4. Therefore, the range of reaction conditions represented by Example 1 can be considered as the optimal conditions. Compared with the embodiment, the product of Comparative Example 1 is pure NaP molecular sieve under the reaction conditions without an activation step; the product of Comparative Example 2 is NaP and NaX molecular sieves under the reaction conditions without a crystallization step, indicating that activation and crystallization are essential key steps for preparing analcime from lithium slag. The NaOH solution concentration of Comparative Example 3 is lower than the minimum concentration required by the reaction conditions, and the resulting product is a NaP molecular sieve, indicating that the NaOH solution concentration is a key factor affecting the product type. The activation time of Comparative Example 4 is shorter than the activation reaction time, and the resulting product is a NaP molecular sieve, indicating that the activation time is a key factor affecting the product type.

[0078] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.

Claims

1. A method for preparing analcime using lithium slag, characterized in that: The steps include: (1) Acid washing and impurity removal: the lithium slag is mixed with an inorganic acid solution, stirred and reacted at 50-70° C. for 0.5-3 h, and then filtered, washed, and dried in sequence to obtain the lithium slag after impurity removal; (2) Activation: Mix the impurity-removed lithium slag with a NaOH solution, react at 75 to 95° C. with continuous stirring for 35 to 72 hours, and age for 10 to 30 minutes to obtain a colloid mixture; (3) Crystallization: subjecting the colloid mixture to a hydrothermal reaction at 110-130° C. for 24-72 hours, and then filtering, washing, and drying in sequence to obtain analcime crystal material; In step (1), the SiO2 content in the lithium slag after impurities removal is 30% to 70%, and the Al2O3 content is 20% to 40%; In step (2), the solid-to-liquid ratio of the lithium slag after impurities removal to the NaOH solution is 1 g: (50-150) mL; In step (2), the concentration of the NaOH solution is 0.6-1.0 M.

2. The method for preparing analcime using lithium slag according to claim 1, characterized in that: The lithium slag is the lithium slag obtained after lithium is extracted by leaching spodumene with sulfuric acid method; the particle size of the lithium slag is ≤200 mesh.

3. The method for preparing analcime using lithium slag according to claim 1, characterized in that: In step (1), the inorganic acid is at least one of hydrochloric acid, sulfuric acid and nitric acid; the concentration of the inorganic acid solution is 0.08-0.5 M; and the solid-liquid ratio of the lithium slag to the inorganic acid solution is 1 g:(10-20) mL.

4. The method for preparing analcime using lithium slag according to claim 1, characterized in that: The SiO2 content in the lithium slag after impurities removal in step (1) is 60% to 70%, and the Al2O3 content is 25% to 30%.

5. The method for preparing analcime using lithium slag according to claim 1, characterized in that: In step (2), the activation reaction temperature is 85-95°C and the time is 40-50 hours.

6. The method for preparing analcime using lithium slag according to claim 1, characterized in that: In step (2), the concentration of the NaOH solution is 0.7-0.9 M.

7. The method for preparing analcime using lithium slag according to claim 1, characterized in that: In step (3), the hydrothermal reaction temperature is 120-130° C., and the reaction time is 36-50 hours.

Citation Information

Patent Citations

  • Method for reconstructing and synthesizing analcime mesoporous material by using coal gangue

    CN115231585A

  • Method for preparing analcime from silicon-aluminum tailings

    CN115818659A

  • Method for preparing Na-A / X or Na-A / X / P cocrystal molecular sieve through lithium slag hydrothermal synthesis

    CN103253681A

  • Alkali grinding activation-based analcime as well as preparation method and application thereof

    CN119284919A

Cited By

  • Composite biochar water adsorbent and preparation method thereof

    CN120550778A

  • Heavy metal wastewater treatment agent and preparation method thereof

    CN121198251A